Assessing households’ knowledge, attitude and behaviour and their welfare changes for the air quality improvement: a case study in Klang Valley, Malaysia - Sarabdeen, Masahina; Rafia, Afroz; A. C., Muhammadu Kijas; Ali, Zaiton (Serials Publications, 2017)
Respiratory diseases are among the highest ranked diseases with the elderly and children the most vulnerable to air pollution in Malaysia. Land transportation contributes most to air pollution in Malaysia. To address this, the study focuses on assessing households’ knowledge, attitude and behaviour and their welfare changes for improved air quality in Klang Valley. The Contingent Valuation Method (CVM) is utilised to estimate the willingness to pay (WTP) to assess the welfare changes for the new air quality improvement plan. The results show that the level of awareness and attitude towards air pollution is high among the household respondents. However, the behaviour of the respondents is very low. Number of sick days, air pollution index, medical expenditure, outdoor activities, ethnic, city, age, and respiratory symptoms are significant factors that affect the welfare changes for air quality improvement plan. Households are willing to pay an average 23 cents extra for one-liter of fuel, which is welfare change for the new alternative air quality improvement plan.